2022
DOI: 10.3389/fnhum.2022.959523
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of abnormal dynamic spontaneous brain activity in patients with high myopia via dynamic regional homogeneity analysis

Abstract: AimPatients with high myopia (HM) reportedly exhibit changes in functional brain activity, but the mechanism underlying such changes is unclear. This study was conducted to observe differences in dynamic spontaneous brain activity between patients with HM and healthy controls (HCs) via dynamic regional homogeneity (dReHo) analysis.MethodsResting-state functional magnetic resonance imaging (rs-fMRI) scans were performed on 82 patients with HM and 59 HCs who were closely matched for age, sex, and weight. The dRe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“… Huang et al (2018a) revealed that the whole-brain gray matter volume of the right cuneus gyrus was decreased in patients with HM, indicating potential visual cortex functional impairment. Our previous study demonstrated that HM patients had altered dynamic regional homogeneity values in the left fusiform gyrus, right inferior temporal gyrus, right Rolandic operculum, right postcentral gyrus, and right precentral gyrus ( Ji et al, 2022 ). Thus far, research has mainly focused on changes in static brain activity in HM patients; and it is believed that the functional interaction of brain regions remains unchanged in time during the whole MRI scan, which is obviously not objective.…”
Section: Introductionmentioning
confidence: 99%
“… Huang et al (2018a) revealed that the whole-brain gray matter volume of the right cuneus gyrus was decreased in patients with HM, indicating potential visual cortex functional impairment. Our previous study demonstrated that HM patients had altered dynamic regional homogeneity values in the left fusiform gyrus, right inferior temporal gyrus, right Rolandic operculum, right postcentral gyrus, and right precentral gyrus ( Ji et al, 2022 ). Thus far, research has mainly focused on changes in static brain activity in HM patients; and it is believed that the functional interaction of brain regions remains unchanged in time during the whole MRI scan, which is obviously not objective.…”
Section: Introductionmentioning
confidence: 99%
“…One of the common causes of vision impairment in the world is myopia. Myopia is alarmingly on the rise which negatively affects both the economic well-being of nations and the quality of life around the globe mainly due to high academic pressure and indoor time spent [1,2,3]. The high prevalence of myopia leads to an increased incidence of high myopia as these two are closely related diseases [3].…”
Section: Introductionmentioning
confidence: 99%
“…Myopia is alarmingly on the rise which negatively affects both the economic well-being of nations and the quality of life around the globe mainly due to high academic pressure and indoor time spent [1,2,3]. The high prevalence of myopia leads to an increased incidence of high myopia as these two are closely related diseases [3]. and ischemia, choroidal neovascularization, macular changes and hemorrhage, and myopic foveoschisis [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations